Immunological responsiveness of chinchillas to outer membrane and isolated fimbrial proteins of nontypeable Haemophilus influenzae. - Bakaletz, L O (1989)
Thin, nonhemagglutinating fimbriae have been demonstrated on 100% of the clinical isolates of nontypeable Haemophilus influenzae recovered from children with chronic otitis media tested in this laboratory (L. O. Bakaletz, B.M. Tallan, T.M. Hoepf, T.F. DeMaria, H.G. Birck, and D.J. Lim, Infect. Immun. 56:331-335, 1988). Chinchillas with induced otitis media responded to this surface-located antigen of both the infecting and a heterologous strain. Antibodies were found in both serum and middle ear fluids.